Tomographic evaluation of dentoskeletal effects of rapid maxillary expansion using Haas and Hyrax palatal expanders in children: A randomized clinical trial - Araújo, Marília-Carolina (J Clin Exp Dent, 2020)
BACKGROUND: Rapid maxillary expansion (RME) is a usual procedure for correcting the transversal maxillary deficiency. Among the most used appliances are the Haas type (tooth-tissue-borne) and Hyrax (tooth-borne) whose main difference is the design. This study aimed to evaluate the dentoskeletal effects of RME using two different expanders in children. MATERIAL AND METHODS: The sample was composed of 42 children of both gender presenting unilateral or bilateral posterior crossbite with mean age 9.49 (SD± 1.35). Patients were randomized into two groups according to the type of expander: Hyrax (n= 21, 9 boys and 12 girls) and Haas (n= 21, 11 boys and 10 girls). Multiplanar coronal and axial slices obtained from cone-beam computed tomography images (i-Cat, Hartsfield, PA, USA) were used at pretreatment (T1) and after 6 months when the expander was removed (T2). Measurements were performed on Dolphin Imaging Systems 11.7 software (Chatsworth, California, USA). The following variables were evaluated: inclinations of the posterior teeth, transverse skeletal widths, length of maxillary dental arch, buccal bone thickness and level of buccal alveolar crest. Statistical analysis performed using chi-squared test to compare the sex ratios between groups and independent t test with the Bonferroni correction for multiple tests. RESULTS: RME increased all maxillary transverse dimensions, regardless of the type of expanders used. Subjects in the Hyrax group experienced significantly increase in the lingual bone thickness (0.94 mm) compare to Haas group (0.21 mm). CONCLUSIONS: The Hyrax-type expander produced greater increase in the lingual bone thickness than did the Haas-type expander, but this effect might not be clinically significant. Both appliances presented similar transversal gain and tended to produce similar orthopedic and orthodontic effects. Key words:Cone-beam computed tomography, palatal expansion technique, palate.